Scalable production of few-layer boron sheets by liquid-phase exfoliation and their superior supercapacitive performance - Li, Hongling (2019)
Although two-dimensional boron (B) has attracted much attention in electronics and optoelectronics due to its unique physical and chemical properties, in-depth investigations and applications have been limited by the current synthesis techniques. Herein, we demonstrate that high-quality few-layer B sheets can be prepared in large quantities by sonication-assisted liquid-phase exfoliation. By simply varying the exfoliating solvent types and centrifugation speeds, the lateral size and thickness of the exfoliated B sheets can be controllably tuned. Additionally, the exfoliated few-layer B sheets exhibit excellent stability and outstanding dispersion in organic solvents without aggregates for more than 50 days under ambient conditions, owing to the presence of a solvent residue shell on the B sheet surface that provides excellent protection against air oxidation. Moreover, we also demonstrate the use of the exfoliated few-layer B sheets for high-performance supercapacitor electrode materials. This as-prepared device exhibits impressive electrochemical performance with a wide potential window of up to 3.0 V, excellent energy density as high as 46.1 Wh/kg at a power density of 478.5 W/kg, and excellent cycling stability with 88.7% retention of the initial specific capacitance after 6000 cycles. This current work not only demonstrates an effective strategy for the synthesis of the few-layer B sheets in a controlled manner but also makes the resulting materials promising for next-generation optoelectronics and energy storage applications.